Structural characterization of some N‐phenyl‐4‐oxo‐4H‐2‐chromone carboxamides. Issue 3 (21st May 2013) - Gomes, Ligia Rebelo; Low, John Nicolson; Cagide, Fernando; Gaspar, Alexandra; Reis, Joana; Borges, Fernanda
<x xml:space="preserve">Abstract</x> N‐phenyl‐4‐oxo‐4H‐2‐chromone carboxamides were found to be inactive as MAO inhibitors in contrast with their N‐phenyl‐4‐oxo‐4H‐3‐chromone carboxamide isomers. In order to obtain a close insight into the docking mechanism for this family of compounds, the molecular and supramolecular structures of nine N‐phenyl‐4‐oxo‐4H‐2‐chromone carboxamides were determined. It was found that, in most of the secondary structures, the N(amido) and the O(carboxyl) of the carboxamide residue participate in strong intramolecular interactions, with the O atom of the chromene ring and with the H(ortho)—C (phenyl), respectively. When the phenyl ring had accessible acceptors as substituents a third intramolecular hydrogen bond was also observed. As a consequence, rotations of the chromone and phenyl rings around the N—C(alpha) and C(alpha′)—C=O are constrained and the compounds were found to be more planar than would otherwise be expected. The deviation from planarity of the whole molecule can be quantified by the dihedral angles between mean planes of the aromatic rings and it was found that they were mainly affected by the degree of torsion of the phenyl ring with respect to the amide residue. The molecular conformations assumed by the secondary amides clearly contrast with that of a related tertiary amide that was also determined in this study. The unavailability of the N in this compound as a donor strongly influences the molecular isomerism and conformation. This analysis demonstrates that the molecules can be classified into four groups depending on the types of interactions formed as described above. If the secondary N(amido) of the carboximide is involved in two intramolecular interactions then this atom does not form any intermolecular contacts. In all other cases it does and the supramolecular structure formed is in most cases supplemented by weak C—H...O interactions.